Morphological evaluation of ultralow density microcellular foamed composites developed through CO2-induced solid-state batch foaming technique utilizing water as co-blowing agent. Issue 4 (July 2020) - Dugad, Rupesh; Radhakrishna, G; Gandhi, Abhishek
In this work, microcellular acrylonitrile-butadiene-styrene foams were developed with utilization of water as a co-blowing agent and CO2 as the primary blowing agent through the solid-state batch foaming process. The effect of saturation parameters with the content of the co-blowing agent has been studied extensively for various foaming attributes. The co-blowing agent enhanced the average cell size and the expansion ratio which are useful for better thermal insulation. The maximum expansion ratio of 29.9 obtained from the effect of saturation temperature and co-blowing agent, 23.6 from the effect of saturation pressure and co-blowing agent, and 22.4 from the effect of saturation time and co-blowing agent. The co-blowing agent significantly affects the cell morphology of polymeric foam with saturation parameters.